2013
DOI: 10.1002/ijc.28036
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic antigen‐related cell adhesion molecule 1 negatively regulates granulocyte colony‐stimulating factor production by breast tumor‐associated macrophages that mediate tumor angiogenesis

Abstract: CEACAM1, a cell adhesion molecule expressed on epithelial cells and activated immune cells, is down-regulated in many cancers and plays a role in inhibition of inflammation in part by inhibition of G-CSF production by myeloid cells. Since macrophages are associated with a poor prognosis in breast cancer, but play important roles in normal breast, we hypothesized that CEACAM1 down-regulation would lead to tumor promotion under inflammatory conditions. Co-cultures of pro-inflammatory M1 macrophages with CEACAM1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
(111 reference statements)
1
14
0
Order By: Relevance
“…M1 macrophages appear to have a proangiogenic function early in tumorigenesis [ 33 ], when the tumor needs blood vessels formation to grow; this fact supports the idea of the role that M1 plays in the early stages of breast tumor formation and it seems to be one of the first immune cells present in the inflammatory process. But, in advanced breast cancers, macrophages resemble the M2 phenotype, while M1 phenotype has not been found; this is the reason why TAMs are generally related more to a M2 phenotype than M1.…”
Section: Discussionmentioning
confidence: 68%
“…M1 macrophages appear to have a proangiogenic function early in tumorigenesis [ 33 ], when the tumor needs blood vessels formation to grow; this fact supports the idea of the role that M1 plays in the early stages of breast tumor formation and it seems to be one of the first immune cells present in the inflammatory process. But, in advanced breast cancers, macrophages resemble the M2 phenotype, while M1 phenotype has not been found; this is the reason why TAMs are generally related more to a M2 phenotype than M1.…”
Section: Discussionmentioning
confidence: 68%
“…For IL-6 release analysis, cells were treated with 500ng/mL LPS over time in the figure and supernatants were collected and analyzed using cytometric bead array. The concentration of inflammatory cytokines was measured using cytometric bead array (CBA; BD Biosciences, USA) as described previously 74 .…”
Section: Flow Cytometry and Cell Sortingmentioning
confidence: 99%
“…The lack of ceacaM1 expression in breast tumors promoted the secretion of high levels of G-cSF by TaMs, which in turn promoted tumor angiogenesis and initial tumor establishment. it has been suggested that G-cSF plays an important role in tumor promotion induced by ceacaM1 downregulation (50). Generally, as shown in Fig.…”
Section: Role Of Tumor Microenvironment In the Effect Of G-csf On Brementioning
confidence: 87%
“…Protease-activated receptor (Par) 2 stimulates G-cSF expression in breast cancer and Par2 gene knockdown or Par2 antagonist use can reduce G-cSF secretion (49). carcinoembryonic antigen-related cell adhesion molecule (ceacaM) 1 expression in breast cancer McF-7 cells inhibits G-cSF secretion by M1 macrophages (50). in addition, G-cSF is the main downstream mediator of the mammalian target of rapamycin (mTor) pathway during the induction of myeloid-derived suppressor cell (MdSc) formation in breast cancer and Welte et al (51), suggested that the regulation of G-cSF by mTor may occur at the transcriptional level.…”
Section: Regulation Of G-csf Gene Expressionmentioning
confidence: 99%